Research on the fast charging of VRLA - Wu Tiezhou; Cao Quan; Liu Lunan; Xiao Qing; Wang Xieyang (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
VRLA can be the energy storing device of the HEV (Hybrid Electric Vehicle), photovoltaic system and so on. The most important factor that restricts the improvement of these fields is the service lifetime of the battery cannot reach the expectation. In the charging process, traditional charging method has serious polarization phenomenon. It will decrease its service life. Aimed at the purpose of reducing the polarization phenomenon, this paper proposed the changing current depolarization pulse charging method which is combining the dynamic model of the battery on the basis of analyzing the existential issues in the pulse charging method. By building the hardware circuit to achieve the function and verify their feasibility. The results indicate that, compared with pulse charging method, the new method makes battery fully charged in shorter time obviously and the temperature of batteries rise more slowly. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1560